Changing seasonality of birth–a possible environmental effect. Issue 5 (October 1993) - Russell, D; Douglas, A S; Allan, T M
Abstract : STUDY OBJECTIVE–Seasonality of birth was examined to determine whether this has changed over the last half century. DESIGN–Time-series analysis was carried out on retrospective data, both for the full 50 year period and for the five decades within that period. Although the primary objective was to investigate seasonality by fitting an appropriate model and examining changes over the period studied, non-seasonal trends were also examined. SETTING–Data by month were obtained from the Registrar General on all births in Scotland during the years 1938-87. SUBJECTS–There was a total of 4, 325, 000 births in the 50 years examined. MEASUREMENTS AND MAIN RESULTS–There are two peaks to the seasonality rhythm–one wide, in spring/early summer and one narrow, in October. Cosinor analysis, modified to allow for the second peak, was used to fit a sine curve model. Analysis of variance showed that this was adequate and established the significance of both peaks. The main peak of seasonal excess rose to a maximum in 1948-57, and thereafter declined by two thirds. While the position of the main peak moved forward two months over the 50 years, the October peak remained unchanged until the final decade, when it rose slightly; thus its relative importance increased steadily from 1948 onwards. CONCLUSIONS–The changing biological rhythm may be related to alterations in the climate and environment or to social differences.